Midwifery Care for Pregnant Women Mrs. S G: Ii P: I A: 0 26 Weeks of Pregnancy with Hypertension in Pregnancy at The Gabriel Medical Center Clinic, Sentang District, Asahan District - Febriani Tarigan, Dwi Feni Febriani; Miranda, Zhannah (Institute of Accounting Research and Novation (IARN), 2022)
Hypertension or high blood pressure is a condition when blood pressure is at a value of 130/80 mmHg or more. This condition can be dangerous, because the heart is forced to pump blood harder throughout the body, which can result in various diseases, such as kidney failure, stroke and heart failure.This method uses the case method with observation and interviews.Pregnant mother Mrs. S carried out laboratory examinations and immediate treatment by regulating the diet and types of food that need to be avoided in pregnant women with hypertension. In this step there is no gap between the theoretical review and the case review.